Generational compensation preferences in cement logistics: insights from gen X, Y, and Z employees - Sulistiawati, Lia; Yuliana, Yayu; Dermawan, A Rengga; Saluy, Ahmad Badawi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
This qualitative study investigates generational differences in compensation preferences among employees in a cement logistics warehouse, focusing on Generations X, Y, and Z. Data were collected through semi-structured interviews and analyzed thematically. Findings reveal distinct patterns: Generation X favors stability, predictable salary increases, and established benefits; Generation Y values competitive pay, promotion-based raises, and benefit equity; and Generation Z prioritizes market-aligned salaries, customizable benefits, and flexible work. While the current system delivers stability for Generation X and transparency for Generation Y, it lacks the flexibility, modernization, and equity sought by younger cohorts. Fairness perceptions are mixed, with younger employees more aware of inequities toward contract staff. Limited to one organizational context and qualitative design, the study offers the insights for adopting generationally responsive HR strategies that balance stability with flexibility, modernized benefits, and participatory policy-making to improve motivation, retention, and performance.